2022
DOI: 10.1002/ange.202215687
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Electroreduction of CO2over Cationic Covalent Organic Frameworks: Hydrogen Bonding Effects of Halogen Ions

Abstract: We present the first example of charged imidazolium functionalized porphyrin-based covalent organic framework (Co-iBFBim-COF-X) for electrocatalytic CO 2 reduction reaction, where the free anions (e.g., F À , Cl À , Br À , and I À ) of imidazolium ions nearby the active Co sites can stabilize the key intermediate *COOH and inhibit hydrogen evolution reaction. Thus, Co-iBFBim-COF-X exhibits higher activity than the neutral Co-BFBim-COF, following the trend of F À < Cl À < Br À < I À . Particularly, the Co-iBFBi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…Besides, the current density of {PV 4 } 2 in CO 2 saturated electrolyte solution was higher than that of {PV 4 } 2 in Ar saturated electrolyte solution, indicating the current increase originated from the reaction of Carbon Dioxide Reduction (CO 2 RR). 31,32 The CO 2 gas adsorption data of the catalysts (Fig. 3i) was consistent with the Type I Langmuir adsorption model, 33,34 indicating that the adsorption behaviour was monolayer adsorption.…”
Section: Photoelectrochemical Properties and Gas Adsorption Character...supporting
confidence: 70%
“…Besides, the current density of {PV 4 } 2 in CO 2 saturated electrolyte solution was higher than that of {PV 4 } 2 in Ar saturated electrolyte solution, indicating the current increase originated from the reaction of Carbon Dioxide Reduction (CO 2 RR). 31,32 The CO 2 gas adsorption data of the catalysts (Fig. 3i) was consistent with the Type I Langmuir adsorption model, 33,34 indicating that the adsorption behaviour was monolayer adsorption.…”
Section: Photoelectrochemical Properties and Gas Adsorption Character...supporting
confidence: 70%
“…Recently, Huang et al reported a porphyrin-based Co-iBFBim-COF-X (X = F − , Cl − , Br − , I − ). 158 Co-iBFBim-COF-I exhibited a high FE(CO) of 99% at a low full-cell voltage of 2.3 V and achieved a high CO partial current density of 52 mA cm −2 with a TOF of 3018 h −1 at 2.4 V. The free halogen anions were beneficial in stabilizing the intermediates via hydrogen bonds and suppressed HER to increase selectivity toward CO 2 RR. Likewise, Liu et al synthesized CoTAPP-PATA-COF by using 5,10,15,20-tetrakis-(4aminophenyl)porphinato]cobalt [TAPP(Co)] and 4,4′,4″,4‴-[1,4-phenylenebis(azanetriyl)]tetrabenzaldehyde (PATA) as monomers (Figure 3k).…”
Section: Cof-based Sacs For Electrocatalytic Energy Applicationsmentioning
confidence: 99%
“…Ionic COFs benefit catalytic reactions by improving their electron conductivity and transfer. Recently, Huang et al reported a porphyrin-based Co-iBFBim-COF-X (X = F – , Cl – , Br – , I – ) . Co-iBFBim-COF-I exhibited a high FE(CO) of 99% at a low full-cell voltage of 2.3 V and achieved a high CO partial current density of 52 mA cm –2 with a TOF of 3018 h –1 at 2.4 V. The free halogen anions were beneficial in stabilizing the intermediates via hydrogen bonds and suppressed HER to increase selectivity toward CO 2 RR.…”
Section: Cof-based Sacs For Electrocatalytic Energy Applicationsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] The atomic level predesign of these structures offers controllable porosity and assembled functional groups in two and three dimensions. [8][9][10][11][12] Moreover, COFs have been used in various applications, such as medical delivery, [13][14][15] gas adsorption and separation, [16][17][18] energy storage and conversion, [19][20][21][22][23][24][25][26] and heterogeneous catalysis [27][28][29][30][31] using different electrocatalytic building units, including metal porphyrins or phthalocyanines. They have also been extensively applied to the oxygen reduction reaction (ORR), [32][33][34][35][36][37] oxygen evolution reaction, [38][39][40][41] and CO 2 reduction reaction.…”
Section: Introductionmentioning
confidence: 99%